Abundance of Microplastic in Water Column of Lubuk Siam Lake (Oxbow) Lubuk Siam Village Siak Hulu District Kampar Regency Riau Province - Helfira, Vivi; Fauzi, Muhammad; Yuliati, Yuliati (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Microplastics originated from degraded plastic materials that may be flown to water bodies and accidentally swallowed by aquatic organisms. The Research aims to understand the microplastics in the water body in the Lubuk Siam lake and was conducted from September to November 2020. Samplings were conducted 3 times, once per month, in 3 sampling points. At each sampling point, 100 L of water was taken and filtered using a planktonnet (30 µm mesh size). To obtain the microplastics, the filtered water was again filtered using Whatman filter paper No.42, and the type of microplastics were identified using a binocular microscope. Results show the types of microplastics found in the water namely fibers, films, and fragments. The microplastic density was (10 fibers/m3), (93 films/m3) and (40 fragments/m3) in the water. Data obtained indicate that the most common type of microplastic found in the waters was film.